Bones at a crossroads : integrating worked bone research with archaeometry and social zooarchaeology - Wild, Markus; Thurber, B. A. (Beverly A.); Rhodes, Stephen; Gates St. Pierre, Christian (Sidestone Press, 2021)
Bone tool studies are at a crossroads. A current path is to go beyond the concatenation of methods or concepts borrowed from other disciplines and aim instead at a truly integrated approach that is more in line with the objectives of interdisciplinary and transdisciplinary research. The papers in this volume follow this direction by adopting various forms of dialogue and integration between old and new methods and approaches, including technological analysis,